On classification approaches, terminology and modern principles of treatment of pathologies associated with high myopia. Part 3. Approaches to monitoring and treatment of patients - V. V. Neroev; O. V. Zaytseva; E. P. Tarutta; E. V. Bobykin; M. A. Kovalevskaya; R. R. Fayzrakhmanov; P. A. Nechiporenko (Российский офтальмологический журнал)
High myopia is a common ametropia associated with a significant risk of multiple comorbidities. Decreased visual functions of myopic patients may be caused by non-specific diseases such as cataracts, glaucoma and rhegmatogenous retinal detachment, which are very likely in myopia. Yet especially important are the specific changes such as atrophic, traction and neovascular manifestations of pathological myopia, the totality of which is defined as myopic macular degeneration or myopic maculopathy. The review highlights current approaches to the diagnosis and treatment of various diseases associated with high myopia, including original schemes for managing patients with myopic choroidal neovascularization and myopic traction maculopathy, developed by experts from the Expert Council on Retinal and Optic Nerve Diseases of the Russian nationwide public body Association of ophthalmologists, and includes an information leaflet for patients.